Mengenal Sistem Pernapasan Manusia Secara Lengkap Beserta Fungsi Organ-Organ yang Berperan di Dalamnya - Diajeng Nur Syabillah; Muhammad Suwignyo Prayogo; Athiyah Husniah El Hilaliyah; Novi Syifaul wijayanti (Publikasi Inspirasi Indonesia, 2026)
The human respiratory system is a vital system that plays an important role in maintaining life through the process of gas exchange between oxygen and carbon dioxide. This study aims to comprehensively examine the human respiratory system, including the structure of organs, the function of each organ, the mechanism of respiration, and the factors influencing its performance. The method used in this research is a literature study by reviewing various scientific sources such as textbooks and relevant journal articles. The results show that the respiratory system consists of integrated organs, including the nose, pharynx, larynx, trachea, bronchi, bronchioles, and lungs, which work synergistically in the process of respiration. The respiratory mechanism involves two main processes, namely inspiration and expiration, which occur due to changes in volume and pressure in the thoracic cavity and are regulated by the nervous system. In addition, external factors such as air pollution and smoking habits can affect respiratory function, while a healthy lifestyle can improve lung capacity. This study contributes to providing a more integrated and contextual understanding, thereby increasing public awareness of the importance of maintaining respiratory system health in daily life.